2005
DOI: 10.1136/ijgc-00009577-200501000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Survivin, a novel anti-apoptosis inhibitor, expression in uterine cervical cancer and relationship with prognostic factors

Abstract: A novel inhibitor of apoptosis, Survivin, seems to be involved in the critical steps of cancer onset and progression and may be associated with unfavorable clinical outcome. We investigated the expression of Survivin in patients with cervical intraepithelial neoplasia grade 3 (CIN3) and uterine cervical cancer, to determine whether Survivin expression is related to poor prognosis. Fourteen cases of CIN3, 53 cases of invasive uterine cervical squamous cell carcinoma (SCC), and 11 cases of normal control group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
10
1
Order By: Relevance
“…10,27 To our knowledge, survivin expression of cervical neuroendocrine carcinoma has not been investigated. Although survivin expression may be increased with tumor progression in cervical squamous cell carcinoma, 9,10,27 survivin expression in cervical neuroendocrine carcinoma tended to be inversely associated with the extent of tumor spread in this study. Survivin expression tended to be more frequent in early-stage tumors than in advanced-stage cases.…”
Section: Discussioncontrasting
confidence: 65%
“…10,27 To our knowledge, survivin expression of cervical neuroendocrine carcinoma has not been investigated. Although survivin expression may be increased with tumor progression in cervical squamous cell carcinoma, 9,10,27 survivin expression in cervical neuroendocrine carcinoma tended to be inversely associated with the extent of tumor spread in this study. Survivin expression tended to be more frequent in early-stage tumors than in advanced-stage cases.…”
Section: Discussioncontrasting
confidence: 65%
“…In addition to clinical pathologic predictors, some molecular variables were also reported to be correlated with prognosis in cervical carcinoma, such as CD44v6, survivin, VEGF, EGFR, COX‐2, EphA2, and EphrinA‐1. CD44v6 expression was found to be associated with lymphvascular space invasion, deep stromal invasion (23) ; significant survivin expression was noted in cancer patients with lesion size, lymphvascular invasion, and elevated SCC antigen levels (24) ; cytosol VEGF might be a marker for the status of pelvic lymph nodes in early‐stage cervical carcinoma and an independent prognostic indicator of its outcome (25) . EGFR and COX‐2 might predict the poor survival of patients with SCC, and the increased COX‐2 expression in tumor cells was correlated with a shorter interval to tumor recurrence (26) ; the overexpression of EhpA2 and EphrinA‐1 was also a strong predictor of overall survival (27) .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, gene expression levels of survivin and survivin‐ΔEx3 in malignant cervical samples were statistically higher than those in normal cervical templates. Lee et al (14) reported on the basis of immunohistochemical evidence that survivin was significantly higher expressed in cervical carcinoma groups compared to the normal control group ( P < 0.05) and that survivin could represent a possible new prognostic marker for uterine cervical carcinoma. Espinosa et al (16) demonstrated that gene expression levels of survivin and survivin‐ΔEx3 were upregulated in cervical carcinomas using semiquantitative RT‐PCR.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, gene expression levels of survivin and survivin-ÁEx3 in malignant cervical samples were statistically higher than those in normal cervical templates. Lee et al (14) reported on the basis of (16) demonstrated that gene expression levels of survivin and survivin-ÁEx3 were upregulated in cervical carcinomas using semiquantitative RT-PCR. Moreover, it has been shown that survivin expression increases during cervical carcinogenesis, following a gradient from low-grade squamous intraepithelial lesions to high-grade squamous epithelial lesions (15) .…”
Section: Discussionmentioning
confidence: 99%